Chinese Anti-Republicans Propaganda during COVID-19 Outbreak - Mohammed, Zainab Saad; Al Shamiri, Sadiq Mahdi (Journal of Tikrit University for Humanities, 2024)
The history of the Sino-US relationship has been marked by its turbulence. It moves up and down in accordance with the desires of both sides. This relationship was initially solid under Trump’s presidency, but after the outbreak of COVID-19 it became exceedingly challenging. As a result, media sources generally and newspaper articles specifically reflect this erratic relationship. The purpose of this research is to reveal the conspiratorial agendas promoted by Chinese media against republicans in general and Donald Trump in particular, as it is hypothesized to occur in the selected data. Propaganda is to be used to disclose these agendas. Two articles from the Global Times and China Daily, two Chinese newspapers, are chosen for the analysis of this study. In terms of analysis, the research is intended to be both qualitative and quantitative. The Institute for Propaganda Analysis’ suggested propaganda techniques are the foundation of the qualitative analysis. The frequencies, percentages, and Chi-square are the foundation of the quantitative analysis. The data shows that the most common form of propaganda is card stacking. It serves to disparage Trump and other republicans. The next technique is name-calling, which is mostly employed to disparage the republicans’ action of demonizing China. Besides, different agendas are revealed including: Republicans mounted a rumor offensive and started spreading false conspiracy theories in order to harm China’s reputation abroad, America is significantly dependent on Chinese manufacturing and if republicans maintain their stigmatizing actions, China will respond in a way that will bring catastrophe in the stock market.